New tasks for Italian Supreme Court: preliminary referral and European revocation - Capasso, Valentina (Civil Procedure Review, 2024)
The recent reform of the Italian civil trial also involved the proceedings before the Court of Cassation, with several changes. Among these, the contribution focuses on the two new functions attributed to the Supreme Court (i.e., that of providing an “early” interpretation of the law at the request of the judges of merit and that of examining applications for specific form of reparation brought against domestic judgments already deemed contrary to the ECHR by the Strasbourg Court), highlighting their criticalities.